Lippia alnifolia essential oil induces relaxation on Guinea-pig trachea by multiple pathways. (10th January 2020) - Vilela, Deisy Azevedo Dourado; Silva, Bismarques Augusto Oliveira; Brito, Mariana Coelho; Menezes, Pedro Modesto Nascimento; Bomfim, Horácio Freitas; Duarte-Filho, Luiz Antonio Miranda de Souza; Silva, Tânia Regina dos Santos; Ribeiro, Luciano Augusto de Araújo; Lucchese, Angélica Maria; Silva, Fabrício Souza
Abstract: Ethnopharmacological relevance: Lippia alnifolia Mart. & Schauer, known as "alecrim-do-mato", "alecrim-de-vaqueiro" and "pedrécio", is used in folk medicine as antiseptic and to treat diseases that affect respiratory system, like bronchitis and asthma. Aim of the study: The aim of this work was to investigate the spasmolytic activity and relaxant mechanism of the Lippia alnifolia essential oil (EOLA) on isolated guinea-pig trachea and to correlate with its use in folk medicine. Materials and methods: Leaves from L. alnifolia were collected in Pico das Almas, Chapada Diamantina, situated in the city of Rio de Contas, Bahia, Brazil. EOLA was extracted by hydrodistillation, analyzed by GC/FID and GC/MS and the volatile constituents were identified. Spasmolytic activity was assayed in isolated guinea-pig trachea pre-contracted with carbachol 1 μM or histamine 10 μM. Relaxant mechanism of EOLA was determined comparing concentration-response curves in the presence or absence of different blockers. Results: Chemical analysis revealed the presence of carvone (60 ± 0.8%) as major constituent. EOLA (1–243 μg/mL) relaxed isolated guinea-pig trachea pre-contracted with carbachol 1 μM [EC50  = 53.36 (44.75–63.51) μg/mL] or histamine 10 μM [EC50  = 5.42 (4.42–6.65) μg/mL]. The pre-incubation of 4-aminopyridine in histamine-induced contractions did not alter significantly the relaxant effect of EOLA. However, the presence of cesium chloride, glibenclamide, tetraethylammonium, propranolol, indomethacin, dexamethasone, hexamethonium, atropine, L-NAME, methylene blue or ODQ reduced EOLA relaxant effect. EOLA 18 μg/mL pre-incubation in calcium-free medium reduced histamine-evoked contractions, but did not alter histamine contractions in the presence of nifedipine. Conclusions: Lippia alnifolia essential oil has spasmolytic activity on isolated guinea-pig trachea and its mechanism of action possibly involves the activation of multiple signal transduction pathways, which culminate in potassium channels activation and cytosolic calcium reduction. Graphical abstract: Image 1